2020
DOI: 10.24815/siele.v7i1.16064
|View full text |Cite
|
Sign up to set email alerts
|

Industrial trainees learning experiences of English related tasks at the workplace

Abstract: This study aims to examine (a) the needs and usage of English language by Industrial Trainees at their workplace, (b) the challenges they faced, and (c) the relevance of Diploma in English courses in a public university in Malaysia to their language and communication needs at the workplace. The sample consists of 55 final year Diploma in English students who had just completed their three months of industrial training at various organisations. The data was collected by means of a questionnaire and semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In examining the individual skills required, many claim that the four skills (reading, writing, listening and speaking) are equally important (Adnan, 2019;Alshabeb et al, 2017;Arumugam & Kaur, 2011;Ranasuriya & Herath, 2020). Others reported the perception that productive skills (speaking and writing) are the most essential for business communication (Baklazhenko, 2018;Fareen, 2018;Singh & Raja Harun, 2020). However, there are also others who believe that writing is the most common skill practiced in the workplace (Spence & Liu, 2013), yet some posit that speaking skills are the most needed skill (Moslehifar & Ibrahim, 2012), as it is also the skill that is tested the most among recruiting agencies (Ahmmed et al, 2020).…”
Section: Most Important Communication Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…In examining the individual skills required, many claim that the four skills (reading, writing, listening and speaking) are equally important (Adnan, 2019;Alshabeb et al, 2017;Arumugam & Kaur, 2011;Ranasuriya & Herath, 2020). Others reported the perception that productive skills (speaking and writing) are the most essential for business communication (Baklazhenko, 2018;Fareen, 2018;Singh & Raja Harun, 2020). However, there are also others who believe that writing is the most common skill practiced in the workplace (Spence & Liu, 2013), yet some posit that speaking skills are the most needed skill (Moslehifar & Ibrahim, 2012), as it is also the skill that is tested the most among recruiting agencies (Ahmmed et al, 2020).…”
Section: Most Important Communication Skillsmentioning
confidence: 99%
“…Writing emails (Adnan, 2019;Ahmmed et al, 2020;Chan, 2014;Fareen, 2018;Hee & Zainal, 2018;Masduki & Zakaria, 2020;Ranasuriya & Herath, 2020;Spence & Liu, 2013;Thomas et al, 2016) Writing reports (Ahmmed et al, 2020;Alshabeb et al, 2017;Chan, 2014;Fareen, 2018;Masduki & Zakaria, 2020;Singh & Raja Harun, 2020;Spence & Liu, 2013) Writing business letters (Fareen, 2018;Spence & Liu, 2013) Writing proposals (Spence & Liu, 2013;Thomas et al, 2016) Writing memos (Alshabeb et al, 2017;Ranasuriya & Herath, 2020;Spence & Liu, 2013) Preparing presentation slides (Spence & Liu, 2013;Thomas et al, 2016) One study that examined the competence level required for writing tasks was conducted by Attan et al (2013), who provided written scripts to industry practitioners to obtain their feedback regarding the written quality of the scripts. Based on a scale rating of '1 = Extremely Limited Writer' to '6 = Effective Writer', the study found that the respondents believed a '3 = Functional Writer' could satisfactorily meet the workplace requirements if given extra assistance and time to learn in the workplace.…”
Section: Communicative Tasks Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the importance of English language at the workplace, numerous studies were conducted on the needs for Malaysian students to have good English communication ability (Jalleh et al, 2021;Diana & Su-Hie, 2017;Isarji et al, 2013;Miskam & Saidalvi, 2018;Ngah et al, 2011;Singh & Harun, 2020;Singh et al, 2021;Su-Hie et al, 2017;Talif & Noor, 2009;Vicky et al, 2016). These studies concluded that a Malaysian graduate's employability is being influenced by academic performance as well as their communicative competence, especially using the English language effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, needs analysis has been identified by researchers as well as educators to be one of the important elements to be considered in improving learners' competence or performance either in the context of education or workplace (Jalal, 2016;Singh & Harun, 2020). In defining the term needs, three (3) elements should be looked into which are necessities, lack and wants (Hutchinson & Waters, 1987).…”
Section: Introductionmentioning
confidence: 99%